High-performance control of permanent magnet synchronous motor using a finite-time sliding mode observer and super-twisting algorithm - Nie, Jing; Li, Yong; Li, Gang (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
To enhance the tracking performance of the permanent magnet synchronous motor (PMSM) drive system in the face of changing operating conditions, such as variations in internal parameters and external load disturbances, this study proposed a new composite control strategy that combines the super-twisting sliding mode controller (STSM) with the finite-time sliding mode observer (FTSMO). The proposed methodology synergistically integrates the enhanced tracking precision and robust disturbance rejection properties inherent to the second-order tracking-sliding mode (STSM) controller with an innovative finite-time sliding mode observer (FTSMO), thereby achieving significant improvements in system state estimation accuracy. The stability of the closed-loop PMSM drive system under the STSM+FTSMO framework is thoroughly analyzed and established using Lyapunov theory. The proposed composite control strategy effectiveness is confirmed through both simulations and experimental outcomes. These findings illustrate that the proposed approach significantly surpasses conventional control methods, especially in managing external disturbances within the PMSM system. Significant enhancements are evident in start-up response, robustness against load variations, convergence speed, and steady-state performance.